An assessment of the Philippine Pharmaceutical Industry as a Sectoral Innovation System - Co, Stephen Michael Hao (University of the Philippines Diliman, 2012)
The pharmaceutical industry is large, high-growth, globalized and innovation intensive. Its products are directed to satisfy customer needs in an area-health care-whose importance for the society is fundamental and rapidly increasing. Health care and therapeutics are among the most relevant issues in the definition of the concepts of welfare and democracy in the new century. Indeed, over the last two decades, the world pharmaceutical industry has undergone profound transformations. It has been experiencing a series of technological and institutional shocks that have affected all the stages of the value chain and have led to deep changes in firms' organization and in market structure, within domestic markets, regionally and globally. In 2010, the Philippine pharmaceutical and healthcare industry is valued at over US 3.0 billion dollars. In the 2011 Business Environment Ratings published by Business Monitor International (BMI), the Philippines ranks 11th of the 17 regional markets surveyed in the Asia Pacific region, below Thailand and above Indonesia. The Philippines' pharmaceutical rating is 49.2, which is well below the average of 52.5 for the region. However, there is evidence that the market is maturing, with calls to expand the socialized healthcare system to serve the entire nation (BMI, 2011). As an industry, the pharmaceutical industry reflects the country's business infrastructure and policies. As an indicator of science and technology, the industry reflects the country's state of innovation in the sciences and technologies. Given the facts, the project proponent believes that a stronger pharmaceutical can contribute to the national competitiveness of the country. More and better partnerships between the public and the private sectors, between the academe and the industry, will not only strengthen the healthcare industry, but also contribute to the overall wellbeing of Filipinos. The purpose of this study is to assess the Philippine pharmaceutical industry as a sectoral system of innovation. Currently, the Philippine pharmaceutical industry is not globally competitive. There is no clear coordination within the industry value chain. There is little innovation in this sector. The government does not give priority to the sector. The industry is focused mainly on the domestic market. While the industry has numerous achievements, there are equally as many shortcomings, majority of which are systemic problems present in the actors and institutions that make up the innovation system. Some of the problems have existed for decades. Left unresolved, these problems have compounded into the dilemmas we have now. This paper aims to analyze the Philippine pharmaceutical industry as a sectoral innovation system. The relevant actors and institutions within the system were identified. The activities and gaps within the system were elucidated. Finally, recommendations were offered on how to improve the industry and help it become innovative. Combining qualitative evidence with existing policy, statistical and technological output indicator data will hopefully provide an applicable framework for policy makers and entrepreneurs in the Philippines to meet these challenges of global competition and grasp the opportunities within the industry.